Game as a Method of Environmental Education of a Child with Special Educational Needs - Zviekova, Viktoria (Journal of Danubian Studies and Research, 2023)
The current scale of environmental changes creates a real threat to people’s lives, which makes the problem of changing humanity’s attitude to nature urgent. This goal is served by environmental education, which involves systematic pedagogical activities aimed at developing environmental culture among pupils and students. Therefore, the primary task of teachers and science-pedagogical workers is the formation of environmental knowledge in pupils and students, the education of love for nature, the desire to preserve and increase it, and to cultivate a culture of nature use. The game is one of the most used methods for providing educational services, as it enables successful solving of educational tasks in the field of environmental education of children. The purpose of the article is to provide scientific substantiation and theoretical analysis of modern game forms of ecological education of school-age children, to determine the types of games and the peculiarities of their use in the process of implementing the tasks of environmental education in the institution of extracurricular education.